Pengaruh Konsentrasi Leachate Terhadap Pertumbuhan Tanaman Uji - Irhamni Irhamni; Setiaty Pandia; Edison Purba; Wirsal Hasan (Jurnal Serambi Engineering, 2020)
Poor landfill management and not in accordance with the rules raises serious problems of liquid waste (leachate). One alternative treatment of heavy metal contaminated waste is phytoremediation techniques with aquatic plants. The purpose of this study was to determine the effect of growth on Typha Latifolia test plants using leachate concentrations. The study used the concentration method for diluting V1.N1 = V2.N2 and Regression. The leachate concentrations used were 20%, 40%, 60%, 80% and 100% and control. Observation data focused on the number of tillers, root length, leaf length and number of leaf petals. The results obtained from the observation data the higher the leachate concentration, the lower the number of tillers, root length, number of leaves and number of leaf petals in Typha latifolia test plants. This proves that Typha latifolia plants are hyperaccumulator plants that can grow on leachate.